From brand aversion or indifference to brand attachment: Authors' response to commentaries to Park, Eisingerich, and Park's brand attachment–aversion model1. Issue 2 (17th January 2013) - Park, C. Whan; Eisingerich, Andreas B.; Park, Jason Whan
Abstract: The primary purpose of our target article was to theoretically argue and empirically demonstrate that it is possible to elevate the customer–brand relationships to the desired level of human relationships by offering three types of self‐relevant benefits. In this response, we discuss the major comments provided by each set of commentators, which are insightful and thought‐provoking. It is our hope that this dialogue will open up a new avenue for future research regarding the nature and management of customer–brand relationships.